Clinical user experiences of observation and response charts: focus group findings of using a new format chart incorporating a track and trigger system. Issue 1 (19th November 2014) - Elliott, Doug; Allen, Emily; Perry, Lin; Fry, Margaret; Duffield, Christine; Gallagher, Robyn; Iedema, Rick; McKinley, Sharon; Roche, Michael
Abstract : Background: Optimising clinical responses to deteriorating patients is an international indicator of acute healthcare quality. Observation charts incorporating track and trigger systems are an initiative to improve early identification and response to clinical deterioration. A suite of track and trigger 'Observation and Response Charts' were designed in Australia and initially tested in simulated environments. This paper reports initial clinical user experiences and views following implementation of these charts in adult general medical-surgical wards. Methods: Across eight trial sites, 44 focus groups were conducted with 218 clinical ward staff, mostly nurses, who received training and had used the charts in routine clinical practice for the preceding 2–6 weeks. Transcripts of audio recordings were analysed for emergent themes using an inductive approach. Findings: In this exploration of initial user experiences, key emergent themes were: tensions between vital sign 'ranges versus precision' to support decision making; using a standardised 'generalist chart in a range of specialist practice' areas; issues of 'clinical credibility', 'professional autonomy' and 'influences of doctors' when communicating abnormal signs; and 'permission and autonomy' when escalating care according to the protocol. Across themes, participants presented a range of positive, negative or mixed views. Benefits were identified despite charts not always being used up to their optimal design function. Participants reported tensions between chart objectives and clinical practices, revealing mismatches between design characteristics and human staff experiences. Overall, an initial view of 'increased activity/uncertain benefit' was uncovered. Conclusions: Findings particularly reinforced the significant influences of organisational work-based cultures, disciplinary boundaries and interdisciplinary communication on implementation of this new practice chart. Optimal use of all chart design characteristics will be possible when these broader cultural issues are addressed.